Distribution and ecology of freshwater oyster Etheria elliptica (Lamarck, 1807) in Pendjari River (BeninWest Africa) - LALEYE, PHILIPPE A.; ADANDEDJEAN, DELPHINE (My University, 2022)
Etheria elliptica (Bivalvia, Etheriidae) is the only freshwater oyster occurring widely in tropical Africa and Madagascar. The distribution and ecology of E. elliptica were investigated in Pendjari River, a tributary of Volta basin. Correspondence Analysis and corrected frequencies were performed on bivalve presence/absence data and abiotic factors. Mean density and mean biomass ranged from 0 to 40 ind./m2 and 0 to 3.8 kg/m2, respectively. E. elliptica exhibited a patchy distribution in Pendjari River (Morisita index Iδ =14.8) occurring mostly in middle and downstream sites. Conversely, species was absent in river upstream. Oyster showed a preference for sections of river with hard substrates used for cementation. However, the oyster was encountered also in silty and sandy habitats forming large size colonies. Total Dissolved Solids (TDS) and altitude appeared to be the significant factors affecting oyster distribution in Pendjari River. Oyster was observed both in calm and turbulent sections of the River. Range of water parameters corresponded to ecological requirements for oyster survival and development. E. elliptica showed plasticity for a large range of habitats suggesting its potential for culture in the River. Management strategies based on oyster ecology could ensure its conservation in Pendjari River.
Keywords: Freshwater mollusk; bivalvia; distribution pattern; ecological preferendum.